Impact of mitigation technologies on rainy season pulse crops from climatic abnormalities - Singh, Y. P.; Singh, Sudhir (Indian Farming, 2018)
Appropriate area specific climate resilient technologies can help in coping up with the challenge of climatic variability. Some climate resilient technologies such as cultivation of drought, heat, insect pest resistant/tolerant cultivars, slight modification in crop management practices, adoption of water management technologies, conservation agriculture technologies and better pest management, access to weather forecast can help to increase productivity of pulse. The crop established on bed and furrow for irrigation increases productivity and saving of crop from more water submergence. Similarly, insurance policies promoted to combat and minimize losses during extreme climatic events. Some of these technologies for pulse production are already being practised by farmers in some parts of the country. But there is a need of wide dissemination and adoption of area specific technologies to protect or enhance pulse production. Thus it is concluded that timely adoption of proper technologies and tolerant/resistant cultivars can dilute effect of climatic abnormalities and doubling yield and benefits from rainy season pulse crops.